2018
DOI: 10.1111/jep.12942
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Pharmaceutical Record: A new method for medication reconciliation

Abstract: This tool provided added value for reconciliation, as it quickly identifies regular medications, adherence, and self-medication behaviour. The ePR is essential for conducting a thorough MedRec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, our results indicate that dosing discrepancies are common regardless of how a patient is referred to the ED. This suggests that relying solely on the SMR for a patient's medication history is unsafe, which is supported by several other studies [26][27][28][29]. A valid medication history should include at least two information sources with different perspectives (i.e., prescribing and dispensing) [5,13].…”
Section: Updating the Smr: Possible Solutions And Reflectionsmentioning
confidence: 81%
“…However, our results indicate that dosing discrepancies are common regardless of how a patient is referred to the ED. This suggests that relying solely on the SMR for a patient's medication history is unsafe, which is supported by several other studies [26][27][28][29]. A valid medication history should include at least two information sources with different perspectives (i.e., prescribing and dispensing) [5,13].…”
Section: Updating the Smr: Possible Solutions And Reflectionsmentioning
confidence: 81%
“…A study conducted in a hospital diabetes service in Toulouse, France, used the Electronic Pharmaceutical Record to summarize patients’ medication history, including over-the-counter drugs, dispensed by community pharmacies over the previous 4 months. 16 By using national health insurance card details and linking to a secure Electronic Pharmaceutical Record server, the study reported improved medication reconciliation accuracy. In almost 30% of patients, medication errors that had not previously been identified were able to be detected and rectified.…”
Section: Resultsmentioning
confidence: 96%
“…A number of studies (n = 26) described optimization strategies, implemented as single-component interventions (Table 2). 15–40 Table 2 summarizes the various single-component optimization strategies used in the included studies, highlighting the stage of the ePrescribing process being optimized and the overall reported effectiveness of the intervention on the primary outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Barakat & Franklin, 2020;Burkoski et al, 2019;Cabilan et al, 2017;González-Bueno et al, 2021;Kennedy & Massey, 2019;Küng et al, 2021;Mulac et al, 2021;Risør et al, 2017;Van Der Veen et al, 2018) Electronic Health System -HER Refs. (Amato et al, 2017;Biltoft & Finneman, 2018;Debono et al, 2017;Griffon et al, 2017;Jurado et al, 2018;Kirkendall et al, 2020;Pontefract et al, 2018;Reinhardt et al, 2019;Shah et al, ). In this case, it is necessary configuration by the doctor to input the cycles of the medication into the MBMS device first.…”
Section: Technologiesmentioning
confidence: 99%